Reflections on the Use of the Intermediate Data Structure (IDS) in Historical Demographic Research - Quaranta, Luciana (Historical Life Course Studies, 2021)
The Intermediate Data Structure (IDS) was developed as a strategy aimed at standardizing the dissemination of micro-level historical demographic data. The structure provides a common and clear data strategy which facilitates studies that consider several databases, and the development and exchange of software. Based on my own experiences from working with the IDS, in this article I provide reflections on the use of IDS to create datasets for analysis and to conduct comparative demographic research.